Penataan legatitas usaha bagi UMKM “Minthul Cryspi” di Desa Karangtengah Kecamatan Tuntang - Fauzi, Adnan Ali; Hidayat, Rina Andriani; Arifah, Indirotul Nur; Khasanah, Uswatun; Hakim, Muhammad Khusnul; Winandari, Fadya (Nur Science Institute, 2024)
Karangtengah Village, Semarang Regency has a lot of potential for Micro, Small and Medium Enterprises (MSMEs) which continue to develop. However, for the majority of MSME actors in Karangtengah Village there is no arrangement and no business legality from the government, some business actors even do not know about business legality. In fact, with the existence of MSMEs, business actors are required to have permits for the business activities they carry out, and in this case, the permit required is a Business Identification Number (NIB). One of the MSMEs in Karangtengah Village is the